Evaluasi Peran Dewan Pengawas Syariah di Indonesia - Rusdi Hamka Lubis; Rachmad Saleh Nasution (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2023)
This research discusses the evaluation of the Sharia Supervisory Board's (DPS) role in the context of Islamic finance in Indonesia through a bibliometric approach. The research focuses on the development of literature related to DPS and its impact on Islamic finance. The rapidly evolving literature in Islamic finance (Siddiqui, 2016; Hasan, 2014) highlights the need for evaluating the role of DPS to ensure its effectiveness (Hasan et al., 2020). The study employs bibliometric methods to identify research trends, main topics, and the impact of literature on DPS. Key references include Siddiqui's work (2016) on the development of Islamic finance in Southeast Asia and Hasan's study (2014) on Sharia governance in Islamic banks. Additionally, Khan (2018) and Kettell (2011) provide in-depth insights into Islamic business ethics and the introduction of Islamic finance. Research findings from this analysis reveal literature gaps and affirm the relevance of bibliometric methods in measuring research impact, identifying trends, and addressing literature gaps. The implications support further research development with a focus on underexplored aspects, including regional exploration and cross-country comparisons. Recommendations involve developing alternative evaluation methods, practitioner case studies, and contributions to policy development related to the role of DPS, utilizing specific performance indicators, and exploring technology implementation in the context of Islamic finance. These suggestions are expected to guide future researchers in developing more in-depth and relevant studies in this continuously evolving domain.